Sinergitas Antar Stakeholders dalam Upaya Percepatan Penurunan Angka Stunting di Kota Surakarta - Gusti Agung Tristasya Ayuningtyas; Kristina Setyowati (Universitas Sebelas Maret, 2023)
This research aims to describe the synergy between stakeholders to accelerate the reduction of stunting rates in Surakarta. The background is that the target of zero stunting in Surakarta in 2022 has not been successful because stunting was still detected in Surakarta in February 2022. The Government has extended its zero stunting target to 2024. Of course, synergy is needed because the problem of stunting is not just a problem for one party. The type of research is descriptive qualitative. Researchers used Doctoroff's (1997) synergy theory, namely effective communication, fast feedback, trust, and creativity. Data sources were obtained from primary data in the form of interviews determined through purposive sampling and secondary data using documents, archives, news, and so on. Data collection uses interview and documentation techniques. Data validity using source triangulation Data analysis techniques use the theory of Miles, Huberman & Saldana (2014), including data condensation, data display, and conclusions drawing. The research results show that synergy between stakeholders is still not successful because all parameters have not been fulfilled properly. Miscommunication is still found between the Health Service, DP3AP2KB, and the society. Apart from that, communication between the Health Service and PT Solo Abadi Indonesia is still not effective. The feedback provided by the Health Service was also considered to be insufficiently fast. This shows a lack of trust from PT Solo Abadi Indonesia to the Health Service. On the creativity parameter, new innovation output was also not demonstrated by BAPPEDA, DP3AP2KB, and the Health Service.